Early administration of indomethacin to preterm infants. Issue 3 (March 1986) - Rennie, J M; Doyle, J; Cooke, R W
Abstract : Indomethacin (0.2 mg/kg) or saline was given intravenously during the first 24 hours to 50 preterm infants in a double blind controlled trial. Eight of the control group later required treatment with indomethacin for clinical signs of left to right shunt, but only one in the treatment group (p = 0.03). Treatment with indomethacin prolonged bleeding time, raised serum creatinine concentrations, and was associated with gastrointestinal haemorrhage in seven infants. Five of these had a serum indomethacin concentration greater than 1.0 microgram/ml. There was a significant reduction of the stable metabolite of prostacyclin, 6-ketoprostaglandin F1 alpha, commencing six hours after treatment and lasting for four days. There was no significant difference in the incidence of intraventricular haemorrhage, days of treatment with oxygen or ventilation, or mortality between the two groups.